Co-creation value: From time to time - Barus, Alexander; Martiyanti, Dwi; Sembiring, Hendri; Pakarti, Piji; Fajrillah, Fajrillah (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
This literature review uses a systematic review approach and bibliographic analysis. The data source is google scholar, and the search for article data uses PoP by using the terms: "co-creation", "co-create", "value-in-use" and service-dominant logic. The articles sampled are articles of the Q1 / Q2 category based on the Scimagojr. Books, book sections, conferences, Indonesian and foreign languages ​​(except English) were not included as sample articles. The sample of articles is limited to the period 2014 – 2019. This literature review uses software assistance: Excel, PoP, Mendeley and VOS viewer. Co-creation or the perspective of service-dominant logic has received great attention by researchers and has been studied in a wide variety of research fields. The systematic review that was carried out resulted in several theories that were often used, namely, social exchange theory, social role theory, planned behavior theory, self-identity theory and self-determination theory. Co-creation as a study is implemented in various research contexts, such as: tourism, hospitality and so on. The authors with the most cited articles are: Lusch & Nambisan (2015), with a total of 950 citations. Researchers who produced the most articles in the period 2014 - 2019 are Edvardsson, Bo (12 documents); Brodie, Roderick J. (7 documents). Co-creation variables are generally used as independent and dependent variables, but some researchers have used them as mediating and moderating variables. During the period the samples were taken, qualitative research dominated over empirical test research. The journal with the most prolific publication of articles is the Journal of Business Research. The most prolific publisher is Emeraldinsight.com. China is the country that most often research on co-creation. Co-creation research with a focus on dyadic relationships is still very limited